POSSIBLE IMPACT OF GLOBAL WARMING AND OTHER FACTORS AFFECTING MIGRATION IN RUSSIA WITH EMPHASIS ON SIBERIA - Dets, Igor A. (Quaestiones Geographicae, 2020)
The main issue of the study was to determine the importance of the climate factor for migration flows in Russia, as well as its impact on the intraregional level. The article also discusses the possible prospects that global warming may bring to Siberia. According to the results, the climate factor does not have a crucial influence on the decision to relocate in Russia, but it remains one of the most important, along with economic, social and political factors. At the regional level, the climate factor is less important than the agglomeration factor and others. The impact of global warming has now affected the overall increase in temperatures in Siberia, which is not yet sufficient to generate additional migration flows.